REWARD, LINGKUNGAN KERJA, DAN WORK-LIFE BALANCE DALAM HUBUNGANNYA DENGAN KEPUASAN KERJA KARYAWAN PADA PERUSAHAAN LOGISTIK DI DEPOK - Saragih, Guntur Syahputra; Kusmana, Agus (Bussman Journal : Indonesian Journal of Business and Management, 2025)
This study aims to analyze the influence of rewards, work environment, and work-life balance on employee job satisfaction in a logistics company in Depok City. The background of this research departs from the importance of job satisfaction as an indicator of organizational success, especially in the logistics industry which has the characteristics of dense, risky, and requires high coordination. The research method used is a quantitative approach with the Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis technique through the SmartPLS application. The study population involved 145 employees, all of whom were sampled through the saturated sampling method. The results of the study showed that the work environment had a significant positive effect on job satisfaction, while rewards and work-life balance had no significant effect. These findings reinforce the Job Demands-Resources Model which emphasizes the importance of working conditions as a key resource in improving employee well-being. On the other hand, the insignificance of the influence of rewards and work-life balance shows the existence of contextual factors such as the perception of fairness and limited work flexibility in the logistics sector. Theoretically, this study contributes to the enrichment of the literature on job satisfaction by affirming the role of the work environment as a key determinant. Practically, the results of the study imply that logistics company management needs to prioritize the creation of a safe, comfortable, and supportive work environment, accompanied by a reformulation of a performance-based reward system and a fairer workload management strategy. Thus, this research is expected to be a reference for human resource managers and subsequent researchers in understanding and improving employee job satisfaction in the context of the logistics industry.